EXPERIMENTAL CONSTRAINTS ON DIFFERENTIATION AND H2O ABUNDANCE OF CALC-ALKALINE MAGMAS - Kawamoto T. (My University, 1996)
Partial melting experiments were conducted on a natural high-alumina basalt from the Higashi-Izu volcanoes (47.4 wt.% SiO2; 8.3 wt.% MgO) with 1 and 2 wt.% total H2O at 0.5 and 1 GPa, 1125-875oC. The partial melts produced segregate by capillary action into crimped parts of the capsule, preventing chemical modification of the melt during quenching. Liquid compositions in 1 wt.% total H2O runs at 0.5 GPa mimic the chemical variations of calc-alkaline andesites and dacites associated with the basalt. The residual phase assemblages from 1 wt.% total H2O experiments are consistent with the observed phenocrysts in two pyroxene andesite and hornblende (hb)-orthopyroxene (opx) dacite. In contrast, a clinopyroxene (cpx)-hb rhyolite assemblage is produced in the 2 wt.% total H2O experiments. Although no such cpx-hb rhyolite is found in either Northeast Japan or the Izu-Mariana arc, this type of rhyolite is found in Central America, which is also characterized by high H2O contents in the associated basaltic melts ([1]).The abundance of SiO2 in residual liquids increased from 49 to 54 wt.% in the 25oC interval between 1125o and 1100oC in the 1 wt.% total H2O system, and from 63 to 71 wt.% in the 50oC interval between 975o and 925oC. The first gap between basalt and andesite is generated by a sudden change in the amount of partial melt, and the second gap between andesite and dacite is produced by the formation of hornblende by the consumption of pyroxene, because the SiO2 abundance of hornblende is less than that of pyroxene. These two reaction relations result in the existence of two compositional gaps, between basalt and andesite, and between andesite and dacite, which are recognized in the Higashi-Izu volcano group and many other calc-alkaline volcanoes.
Keywords: MAGMAS; BASALTS; ANDESITES; DACITES; RHYOLITES; WATER; SUBDUCTION